PERAN PENASEHAT AKADEMIK DALAM MEMINIMALISIR PERILAKU PROKRASTINASI AKADEMIK MAHASISWA SEMESTER AKHIR - Okarniatif, Andi Almadani Marennu; Syukur, Muhammad; Najamuddin, Najamuddin (Faculty of Tarbiyah and Teacher Training, 2025)
Final semester students often experience academic procrastination which results in delays in completing their studies. This study aims to examine the role of academic advisors in minimizing academic procrastination behavior of final semester students of the Department of Public Administration, Makassar State University. This study uses a qualitative descriptive approach with a purposive sampling technique. The informants in this study consisted of 11 alumni who graduated on time in the 2021–2023 graduation period and 5 academic advisors whose students successfully completed their studies on time. Data collection techniques were carried out through interviews, observations, and documentation, then analyzed with the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that personal motivation, support from family and peers, and active guidance from lecturers were the main factors that encouraged students to complete their thesis. Meanwhile, low intrinsic motivation, minimal external support, limited resources, and weak time management were the main obstacles. Academic advisors play an important role in providing direction, motivation, emotional support, and intensive mentoring, which help students become more disciplined and focused in completing their final assignments. This study emphasizes the importance of the role of lecturers in the academic process, especially in encouraging timely completion of studies.